The rise of home death in the COVID-19 pandemic: a population-based study of death certificate data for adults from 32 countries, 2012-2021 - Lopes, Sílvia (2024)
During the coronavirus 2019 disease (COVID-19) pandemic, health systems had to respond to the needs of COVID-19 patients, while caring for patients with other life-threatening conditions. Pandemics, such as the COVID-19 pandemic, stir global health and mortality patterns. This is likely to include trends in dying places. In this paper, we examine trends in place of death for adults in 32 countries, comparing the initial COVID-19 pandemic years (2020-2021) with the eight years before the pandemic (2012-2019).